On Λ e^*-Open and Λ e^*-Closed Sets in Topological Spaces and Their Use in Financial Risk Assessment - Gurusamy, Saravanakumar; Majid, Nassar Aiman; Murugaraj, Arun (Journal of the Indonesian Mathematical Society, 2025)
In this paper, the notions of Λ e^*-open and Λ e^*-closed sets are introduced and studied within the framework of general topology. Several fundamental results and characterizations are established, including their relationships with e^*-open sets, regular closed sets, and various separation axioms. The interplay between Λ e^*-sets and classical topological structures is examined through a sequence of lemmas and theorems. Furthermore, the developed concepts are applied to construct a mathematical model for low-risk stock selection. Specifically, the properties of Λ e^*-sets are utilized to filter stocks that maintain topological stability under uncertainty, providing a novel approach to identifying financially stable investment options within a given market.